Antecedent behavior of individual performance among Jabatan Tenaga Kerja Kelantan's Worker / Nur Arina Mat Aziz - Mat Aziz, Nur Arina (2016)
This study was conducted to get a clear view about the task perfonnance, adaptive performance, contextual performance and counterproductive work behaviour can affect the behaviour of individual work performance in Jabatan Tenaga Kerja Negeri (JTK) Kelantan. By classifying the factors, the researcher also could classify the main factor that influenced workers performance at the workplace. This study is in descriptive and correlation research which respondents for this study were the workers at JTK Kelantan. The total respondent were 105 workers and stratified used in this research because it is effective research sampling design. This design provide more information with a given sample size. In this study, the researcher used questionnaires to get all data and the findings were evaluated using the SPSS Data. Lastly, the discussion derived from the findings advised several recommendations and ideas for future research.